2015
DOI: 10.1093/eurpub/ckv224
|View full text |Cite
|
Sign up to set email alerts
|

Health and unemployment: 14 years of follow-up on job loss in the Norwegian HUNT Study

Abstract: People with poor mental and physical health are at increased risk of job loss. This contributes to poor health amongst the unemployed and highlights the need for policy focus on the health and welfare of out of work individuals, including support preparing them for re-employment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 34 publications
(42 reference statements)
4
42
1
Order By: Relevance
“…As health selection to unemployment has been found in previous studies,7–9 11 an increase in the likelihood of purchasing psychotropic drugs around the time of unemployment could be attributed to such a selection process; individuals who develop depression may be more likely to lose their job. It is also possible that people who become depressed or anxious identify their jobs as a source of distress and decide to resign at a period their mental health is deteriorating.…”
Section: Methodsmentioning
confidence: 59%
“…As health selection to unemployment has been found in previous studies,7–9 11 an increase in the likelihood of purchasing psychotropic drugs around the time of unemployment could be attributed to such a selection process; individuals who develop depression may be more likely to lose their job. It is also possible that people who become depressed or anxious identify their jobs as a source of distress and decide to resign at a period their mental health is deteriorating.…”
Section: Methodsmentioning
confidence: 59%
“…Owing to the economic context, new employment patterns and risks in young populations as well as workability in the early old age and other determinants of early exit from the labour force are an important concern,23 albeit working conditions and occupational exposures are major determinants of premature ageing 24–26. While working conditions may lead to impairments and disease, loss of work can also be deleterious for health, and many studies have investigated how unemployment influences mental and physical health and health-related behaviours,27 and how health may influence the risk of becoming unemployed 28. CONSTANCES was designed as a large random sample of the French adult population, it will also provide descriptive information on the health of the French population.…”
Section: Why the Cohort Was Set Up?mentioning
confidence: 99%
“…Previous studies including meta-analyses have found support for both mechanisms. On the one hand pre-existing mental ill health is associated with an increased risk of unemployment [2, 58] and a lower likelihood of re-employment [2, 9, 10]. On the other hand unemployment is followed by poorer [13, 6, 11, 12] and re-employment by improved mental health outcomes [1, 2, 9, 12, 13].…”
Section: Introductionmentioning
confidence: 99%